Analisa Pengendalian Persediaan Bahan Baku pada CV. Es Mitra Jaya Surabaya - Luna Windianto; Wiwik Handayani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Manual data collection of raw materials causes inventory problems such as data collection errors, duplicate data, and warehouse loading processes that consume a lot of time. This research was conducted on a milktea boba frenchise company that is very maintaining quality. Raw materials are provided and arranged by the central company, the time of marking goods can only be ordered according to a predetermined schedule. By implementing the Qr-Code Scan system using the Scan-IT to Office application, the warehouse goods data collection process becomes more effective. The results of system implementation were evaluated using the PIECES method with an average satisfaction of 3.58 (SATISFIED) from the six domains tested. The results of the total cost calculation that have been carried out prove that the decrease in inventory costs using Material Requirement Planning (MRP) with the Economic Order Quantity (EOQ) method has decreased. The calculation carried out by the company shows the total inventory cost of Rp.32,346,426.25. After calculations using the MRP method, it decreased by Rp.1,460,780.23.